Zero Stunting Villages: Analyzing the Challenges and Imperatives of Actor Collaboration - Mahardhani, Ardhana Januar; Darmawan, Dili Arfia; Sunarto, Sunarto; Mufanti, Restu (Universitas Teuku Umar, 2025)
The purpose of this study is to determine the role of the Krebet village government in making Krebet village a zero stunting village in Ponorogo Regency. This type of research uses qualitative methods woth data collection technique of interviews, observation, and documentation. The key informants in this study were the village head, health cadres, and community leaders. The results of this study show that. the Krebet village governments carries out its role by conducting educational socialization, nutrional intervention, increasing access to clean water and sanitation, empowering the family economy, and collaboration with various parties. Krebet village has shown full commitment to reducing stunting rates. Various programs, ranging from counseling, coachong, and socialization, have been implemented. However, the village government realizes that these efforts are not enaough if they only rel yon the budget. The conclusion that can be drawn from the research conducted is that is its implementation, the zero stunting designation was not balanced with role of the actors, so the Krebet village government still has dificulties in making the vallage a zero stunting village. The village government needs active participation from all parties in an effort to solve the stunting problem.